Pengaruh Informasi Akuntansi dan Ketidakpastian Tugas terhadap Perilaku Manajer: sebuah Eksperimen Semu - Fazli Syam BZ; Indra Wijaya Kusuma (The Indonesian Journal of Accounting Research, 2013)
The aim of this research is to predict and explain empirically the effect of accounting information and task uncertainty  on the manager behavior. The research result is expected to give a clearer explanation to the management accounting literatures, and a contribution to the management accounting practitioner in general. The research employed quasi-experimentation as the methodology and used students of MM-UGM as a proxy of the manager as research participants. The research used 120 participants, who were classified into four major different groups randomly depending on whether or not accounting information was used and the level of task uncertainty.The result shows that the uses of accounting information as a tool to assess the achievement and performance of manager in the low task uncertainty, which cause the manager tend to act positively, is not significantly proved. The insignificant result is also showed in the hypothesis that the managers tend to act negatively when the achievement and performance of manager is assessed by accounting information in the situation where the task is uncertain. The assessment of achievement and performance of the manager without using accounting information and when the uncertainty of the task is low which causes the managers to act positively is proved significantly. It means that task uncertainty influential to the manager behavior. Nevertheless, without using accounting information, manager’s achievement and performance assessment under high task uncertainty, which tends to cause managers act positively is not proved. These are consistant with the findings of Otleys (1978) which state that the usage of accounting information (budget constraint style) to assess manager’s achievement and performance will not cause manager’s disfunctional behavior.